The Influence of City Branding and E-Wom On Interest In Visiting Religious Tourist Attractions In Surakarta The Role of The Intervening Variable City Image - Pramesti, Safira Amelia; Sholahuddin, Muhammad (Jurnal Manajemen, 2024)
Religious tourism has become a significant sector of the tourism industry in many countries around the world. Religious tourism sites attract tourists who seek spiritual experiences, religious values, and cultural knowledge. One of the places that has a lot of religious tourism is Surakarta.The purpose of this study was to analyze the effect of City Branding and E-Wom on interest in visiting religious tourist attractions in Surakarta, the role of the intervening variable City Image. This research method is quantitative. This study uses data in the form of primary data. This study uses a questionnaire method to collect data. The population in this study was obtained from the population of tourists in Central Java Province with a total of 1412. The sampling technique is purposive sampling. The number of samples in this study were 150 respondents. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS software. The results of this study are City Branding and E-Wom have a positive and significant effect on City Image. City Branding, E-Wom and City Image have a positive and significant effect on Visiting Interest. City Branding has a positive and significant effect on Interest in Visiting which is mediated by City Image. E-WOM has a positive and significant effect on Interest in Visiting which is mediated by City Image.. The implication of this research is to help people to know more about the factors that influence tourist trust and interest in visiting.